2017
DOI: 10.1002/2016jd025757
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of coal dust from an active mine on the spectral reflectance of Arctic surface snow in Svalbard, Norway

Abstract: Light‐absorbing particles (LAPs) in snow such as dust and black carbon influence the radiative forcing at the Earth's surface, which has major implications for global climate models. LAPs also significantly influence the melting of glaciers, sea ice, and seasonal snow. Here we present an in situ study of surface snow near an active coal mine in the Norwegian Arctic. We couple measurements of spectral hemispherical directional reflectance factor (HDRF) with measurements of LAPs characterized in two ways, as ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 53 publications
0
27
0
1
Order By: Relevance
“…For the data collected here, the depth of the trough related to liquid water absorption is related to the derived whitecap factor for the 980 and 1,200 nm features. A baseline subtraction approach (also referred to as continuum removed) has proven to be robust for many environmental remote sensing applications (Clark, 1999;Dierssen et al, 2015;Khan et al, 2017;Garaba and Dierssen, 2018) and is explored here (Figure 10). The water absorption features at ∼750 nm is not a robust indicator when the whitecap factor is low.…”
Section: Whitecap Modeling For the Pace Sensormentioning
confidence: 99%
“…For the data collected here, the depth of the trough related to liquid water absorption is related to the derived whitecap factor for the 980 and 1,200 nm features. A baseline subtraction approach (also referred to as continuum removed) has proven to be robust for many environmental remote sensing applications (Clark, 1999;Dierssen et al, 2015;Khan et al, 2017;Garaba and Dierssen, 2018) and is explored here (Figure 10). The water absorption features at ∼750 nm is not a robust indicator when the whitecap factor is low.…”
Section: Whitecap Modeling For the Pace Sensormentioning
confidence: 99%
“…[] and snow near a coal mine in Svalbard with refractory BC 345 ppb, effective BC 4900 ppb, reported in Khan et al . []).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Pb was measured at~4-5 times background levels since 1960s [Boutron, 1982;McConnell et al, 2014], and Ba concentration was found to be a factor of 23 greater since 1980 [Korotkikh et al, 2014]. Khan et al [2017]; pollution on snow, [Simões and Zagorodnov, 2001]; and ablation zone in Greenland, [Wientjes and Oerlemans, 2010]). Greater magnitude impurity concentrations on snow and ice can not only be detected with remote sensing but also geochemically differentiated [Gleeson et al, 2010;.…”
Section: Introductionmentioning
confidence: 99%
“…To accurately measure the size distributions of BC in snow in this study, we used a single-particle soot photometer (SP2) based on a laser-induced incandescence technique, combined with a nebulizer (Kaspari et al, 2011;Lim et al, 2014;McConnell et al, 2007;Mori et al, 2016;Sinha et al, 2018;Wendl et al, 2014). The nebulizer/SP2 system has been used to measure the size distribution of BC in snow at Alert in Nunavut, Canada, and at Ny-Ålesund, Woodfjorden, and Mine in Spitsbergen, Norway (Khan et al, 2017;Macdonald et al, 2017;Sinha et al, 2018). In particular, Sinha et al (2018) investigated the seasonal progression of deposition of BC by snowfall at Ny-Ålesund.…”
Section: Introductionmentioning
confidence: 99%